BIOFILM FORMATION ON THE SURFACE OF MATERIALS AND MEDICAL PRODUCTS BY NOSOCOMIAL STRAINS ISOLATED FROM THE BIOLOGICAL SUBSTRATES OF PATIENTS - E. A. Nemets; R. A. Yunes; A. K. Khudoshin; N. I. Gabrielyan; V. I. Sevastyanov (Вестник трансплантологии и искусственных органов)
Aim. To study the ability of hospital-associated strains isolated from the biological substrates of patients oper- ated on under extracorporeal circulation, to form biofilms on the surface of medical materials and products. Materials and methods. The formation of biofilms of strains of Staphylococcus aureus, Serratia liquefaciens, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter spp. isolated from the biological substrates of patients operated on under extracorporeal circulation, on different surfaces (politetraftorotilen, medical poly- ethylene, Polyoxybutirate-to-valerate, silicone, polyvinyl chloride), was studied by a modified method for the surface of the medical materials and products. Results. The influence of the material nature, as well as hydrophi- lization of the surface, on the ability of hospital-associated strains, isolated from the biological substrates of pa- tients operated on under extracorporeal circulation, to form biofilms is studied. It is shown that that certain strains exhibit an increased tendency to biofilm formation on more hydrophobic surfaces, e. g., Acinetobacter spp. At the same time the activity of Staphylococcus aureus on silicon surface (hydrophobic surface) is minimal. Other strains almost equally form biofilms on hydrophilic and hydrophobic surfaces e.g. Serratia liquefaciens. It was also shown that the surface hydrophilization of PEG to 50% for all the studied strains leads to dramatic reduc- tion of biofilm formation. Conclusion. The tendency to form biofilms of a particular hospital-associated strain is individual and depends on the nature of the medical material and physical-chemical characteristics of its surface. Hydrophilization of the surface of the medical material is accompanied by a lowered risk of biofilm formation.